The effect of crystal facets and induced porosity on the performance of monoclinic BiVO4 for the enhanced visible-light driven photocatalytic abatement of methylene blue. Issue 4 (August 2019) - Shafiq, Iqrash; Hussain, Murid; Shehzad, Nasir; Maafa, Ibrahim M.; Akhter, Parveen; Amjad, Um-e-salma; Shafique, Sumeer; Razzaq, Abdul; Yang, Wenshu; Tahir, Muhammad; Russo, Nunzio
Graphical abstract: Highlights: An easy two-step synthesis strategy is designed for mesoporous BiVO4 . Mesoporous silica (KIT-6) is employed as a template for porosity enhancement. KIT-6 provides selective growth of the monoclinic BiVO4 phase. The photocatalytic performance is evaluated under visible-light irradiation. The photocatalytic activity is enhanced, due to selective phase growth and improved porosity. Abstract: In this study, a unique two-step approach has been developed to synthesize mesoporous BiVO4 (m-BiVO4 ) photocatalysts. The synthesized photocatalysts were characterized by means of XRD, SEM, EDS, UV–vis, Raman, PL, DRS, and N2 -physiosorption analysis techniques. The hybrid BiVO4 /KIT-6 composite and m-BiVO4 particles exhibited selective growth of the (040) crystal facet, a smaller size, high surface areas, a large pore volume as a result of the porosity induced by KIT-6 and, a greater number of active sites. The charge recombination rate of m-BiVO4 was remarkably lower than that of conventional BiVO4 . In addition, the bandgap energy of m-BiVO4 was 2.2 eV, which is suitable for visible light irradiation. It was observed that the photocatalytic activity of m-BiVO4 was superior to that of conventional BiVO4 under visible-light illumination, due to the synergistic effect of the highly active monoclinic phase and large surface area of m-BiVO4 . Furthermore, the monoclinic m-BiVO4 was also tested for photocatalytic degradation ability by using an anonymous industrial effluent for 3 h under visible light irradiation.